Democracy and party dominance in Kenya and South Africa : a comparative study of the Kenya African National Union and the African National Congres - Mwangi, Oscar Gakuo (Rhodes University, Faculty of Humanities, Department of Political Studies)
Kenya and South Africa can be described as dominant party systems, under the dominance of the Kenya African National Union CKANU) and the African National Congress CANC) respectively. A dominant party system is in essence a democracy. The spirit of democracy may, however, apparently be contradicted by the weight of party dominance, thus questioning the content of and prospects for democracy under party dominance in both Kenya and South Africa. The study is a comparative analysis of party dominance in Kenya and South Africa. The main objective is to exan1ine the relationship between party dominance and democracy in both countries. It seeks to find out how party dominance is reproducing itself and surviving the post 1990 transition processes in Kenya and South Africa. More importantly, the study also seeks to find out how party dominance impacts upon institutions that support or uphold democratization and subsequently democracy. The findings of the study demonstrate that party dominance has reproduced itself and survived the post-1990 period, and is also impacting upon democratization and democracy. The dominant parties take a similar trajectory in pursuit of dominance over the state and its apparatuses. However, they differ when it comes to their relationship with the civil society. That between KANU and civil society is antagonistic, as the ruling party seeks to augment political power through authoritarian dominance of the latter to, while that of the ANC and civil society is responsive, as the former seeks to enhance political stability in the country. The impact of party dominance upon institutions that support democracy takes similar and different trajectories in both countries. Similarities arise with respect to the detrimental impact upon institutions of the Executive that ensure accountability and transparency, evident in the increasing cases of corruption, nepotism and political patronage appointments. Similarly, there has been a detrimental impact upon the Legislature regarding parliamentary proceedings. Parliamentary committees and opposition parties are being rendered ineffective as organs of ensuring transparency and accountability, and are often subject to delegitimation. The impact of party dominance on the Judiciary, however, differs in both countries. In Kenya, the judiciary continues to suffer from excessive interference from the Executive and the ruling party, whereas in South Africa the judicial system remains largely independent with regard to the application of justice, despite constant criticisms from the dominant party. The study concludes that South Africa is, gradually, going the Kenyan way. If this condition is left unchecked there is the possibility that South Africa could eventually end up a psuedo-democracy like Kenya, where formal democratic political institutions such as multiparty elections, exist to mask the reality of authoritarian dominance. The thesis recommends that strengthening civil society organizations, opposition political parties, and state institutions in both countries to ensure greater accountability and transparency, will reverse this detrimental effect of party dominance. It also recommends meaningful constitutional reforms that will guarantee greater independence of these institutions, and the decentralization of governmental and political power to check and limit the powers of the dominant party. Also recommended are areas for further research.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Kenya African National Union; African National Congress; Political parties -- South Africa; Political parties -- Kenya; Democracy -- South Africa; Democracy -- Kenya -- South Africa -- Politics and government; Kenya -- Politics and government